2018
DOI: 10.1002/ijc.31922
|View full text |Cite
|
Sign up to set email alerts
|

Decreased RORC expression and downstream signaling in HTLV‐1‐associated adult T‐cell lymphoma/leukemia uncovers an antiproliferative IL17 link: A potential target for immunotherapy?

Abstract: Retinoic acid‐related drugs have shown promising pre‐clinical activity in Adult T‐cell Leukemia/Lymphoma, but RORC signaling has not been explored. Therefore, we investigated transcriptome‐wide interactions of the RORC pathway in HTLV‐1 and ATL, using our own and publicly available gene expression data for ATL and other leukemias. Gene expression data from ATL patients were analyzed using WGCNA to determine gene modules and their correlation to clinical and molecular data. Both PBMCs and CD4 + … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…We also found that expression of RORC was comparable in tumor and normal tissues, although its expression level was significantly lower in advanced-stage tumor tissues. RORC is a regulator of the proinflammatory Th17/interleukin-17 axis in adult T-cell leukemia [ 34 ], and low expression of RORC was a negative prognostic indicator of KIRC in our study. Thus, further studies are needed to assess the potential functions and mechanisms of RORC in immunotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…We also found that expression of RORC was comparable in tumor and normal tissues, although its expression level was significantly lower in advanced-stage tumor tissues. RORC is a regulator of the proinflammatory Th17/interleukin-17 axis in adult T-cell leukemia [ 34 ], and low expression of RORC was a negative prognostic indicator of KIRC in our study. Thus, further studies are needed to assess the potential functions and mechanisms of RORC in immunotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…We and others have previously demonstrated that a combined in vitro, ex vivo and in silico approach might recapitulate the ATL in vivo response 16 19 . In addition, we have also shown that HTLV-1-transformed MT-2 and MT-4 cells phenocopy primary ATL cells 18 in their relative resistance to the antiproliferative and proapoptotic effects of IFN-α 16 , 17 .…”
mentioning
confidence: 94%
“…Our molecular understanding of genomics and transcriptomics deregulation following HTLV-1 infection has come from studying ATLL patient samples [ 6 , 20 , 21 ]. Because Tax and HBZ show different expression kinetics during ATLL progression [ 22 ], it has remained challenging to systematically analyze the relative contribution of each viral protein in reprogramming the host cell’s transcriptome and proteome.…”
Section: Introductionmentioning
confidence: 99%